Pengukuran Tingkat Penerimaan Pengguna Mobile Banking menggunakan Unified Theory of Acceptance and Use of Technology (UTAUT) - Madjid, Aulia Nuur; Sari, Shinta Permata (IPM2KPE, 2024)
This study aims to determine and analyze the influence of performance expectations, effort expectations, and social influences on behavioral intentions to use mobile banking, as well as to determine and analyze the influence of facilitating conditions and behavioral intentions on mobile banking behavior. This study uses a quantitative research method with primary data collection. The data collection technique uses a questionnaire. The research data were analyzed using Partial Least Square (PLS) and then processed using SmartPLS 4.0 software. The results of this study indicate that behavioral intentions to use mobile banking are influenced by performance expectations, effort expectations, and social influences, while mobile banking behavior is influenced by facilitating conditions and behavioral intentions. Furthermore, behavioral intentions can mediate the relationship between performance expectations, effort expectations, and social influences on usage behavior. In conclusion, this study is expected to be used by financial technology service providers to develop more effective strategies so that they can help provide features and services that suit user needs. Keywords: Mobile Banking, Behavioral Intentions, Usage Behavior, UTAUT